PERJANJIAN POLA KEMITRAAN DALAM PELAKSANAAN PEREMAJAAN TANAMAN KELAPA SAWIT - Asri Elies Alamanda; Irma Mangar; Lailatul Mutmainah; Nurul Fajriyah (Jurnal Hukum Mimbar Justitia, 2023)
One effort to increase the productivity of oil palm plants is to carry out a replanting program. In implementing the oil palm plant rejuvenation program, most of the planters come from low-educated communities who lack knowledge regarding what and how partnership patterns are. It is the government's authority to regulate cooperative relations between plantation companies and farmers. This collaboration is carried out considering that planters may not be capable enough to work on rejuvenating their oil palm plantations, whereas if oil palm trees that are over 20-25 years old are not rejuvenated, they will no longer be productive and will produce little fruit. This collaboration is carried out by plantation companies as the core and plasma farmers/planters. In implementing this replanting program, there are several models of partnership patterns, one of which is the Intiplasm partnership pattern which is the most popular in implementing this program. The method used in this research is Normative Juridical with the research approach used is qualitative by examining statutory documents and comparing them with conditions in the field. The research results showed that the implementation of Minister of Agriculture Decree Number 940/KPTS/OT.210/10/97 concerning Guidelines for Agricultural Business Partnerships in the Implementation of Oil Palm Plant Rejuvenation has been carried out well, as evidenced by the existence of several regions in Indonesia that have successfully and completed following replanting using the intiplasma partnership pattern. This type of partnership pattern in implementing replanting is very important, because it can help people who do not have funds to continue participating in the replanting program. Then the form of legal protection obtained by farmers if a dispute occurs is through mediation and efforts to resolve disputes outside of court. Then, if no bright spot is found, the problem can then be resolved in court with all the consequences. Keywords: Palm Oil; Rejuvenation; Partnership Pattern.